Constructionism and the Textuality of Social Problems - Del Rosso, Jared; Esala, Jennifer (Qualitative Sociology Review, 2015)
Building on the work of Dorothy Smith and Bruno Latour, this article examines the textual mediation of social problems activities. Because of their materiality and/or digitality, texts preserve constructions of reality, rendering those constructions durable and mobile. This, in turn, allows claims-makers distant in time or space to access those constructions as interpretive resources for claims-making. Texts, then, help us account for how social problems spread and endure. We show how texts mediate claims-makers access to two resources for claims-making: the “reality” of problematic conditions and definitions of problems. We also consider how texts structure social problems work. We conclude by briefly considering how the contemporary technological environment may be altering the textual mediation of claims-making.